Public food transfers during pandemic: Insights from an IFPRI survey in Bangladesh - Chowdhury, Shyamal K.; Bin Khaled, Muhammad Nahian; Raghunathan, Kalyani; Rashid, Shahidur (Financial Express, 2020)
Public food transfer programmes act as a lifeline for many poor households that might otherwise live with constant food insecurity and the threat of hunger. Such programmes are important for the poor and vulnerable in low-income countries such as Bangladesh, but also in high-income countries such as the USA. In the USA in 2019 alone, more than 35 million individuals received food assistance from its largest anti-hunger transfer programme -- the Supplemental Nutrition Assistance Programme (SNAP), formerly known as Food Stamps. In the 2019-20 financial year, in Bangladesh, the Khaddo Bandhob Karmasuchi (Food Friendly Programme, FFP), a similar programme that offers subsidised rice during the lean season twice a year, reached about 5 million households (equivalent to 27.5 million people) at a cost of more than BDT 32.0 billion (source: Directorate General of Food). FFP is the country's largest anti-hunger programme in terms of outreach, and since rice is the main staple providing about 60 per cent of average calorie intake for the poor, the programme is immensely important in ensuring that the poor are able to meet their basic caloric requirements.